Effect of phosphorylated lignin on flame retardancy of polypropylene‐based composites. Issue 28 (4th May 2022) - Lee, Jung‐Hun; Jang, Dawon; Yang, Inchan; Jo, Seong Mu; Lee, Sungho
Abstract: Polypropylene (PP) is a synthetic polymer with excellent physical properties useful for various industries. However, its flammability in air limits its applications. In the present work, lignin filler was modified by phosphorylation, and characterized through chemical, structural, thermal, and morphological analyses. The resultant products were incorporated into PP to increase the flame retardancy of PP‐based composites. Although, the mechanical properties of the PP composites containing 30 wt% filler deteriorated, the tensile strength was maintained. An addition of phosphorylated lignin (pL) into PP decreased the heat release rate from 1136.5 to 777.2 kW/m 2 and the total smoke release from 25.1 to 9.6 m 2 /m 2 . Furthermore, scanning electron microscopy images of the pL incorporated composites after the combustion test revealed that the solid char formed on the composites acted as a protective layer for PP. Thus, incorporating pL into PP is a feasible approach for improving its flame retardancy. Abstract :